Biexciton Formation in Bilayer Tungsten Disulfide - He, Z; Xu, W; Zhou, Y; Wang, X; Sheng, Y; Rong, Y; Guo, S; Zhang, J; Smith, J; Warner, J (American Chemical Society, 2016)
Monolayer transition metal dichalcogenides (TMDs) are direct band gap semiconductors, and their 2D structure results in large binding energies for excitons, trions, and biexcitons. The ability to explore many-body effects in these monolayered structures has made them appealing for future optoelectronic and photonic applications. The band structure changes for bilayer TMDs with increased contributions from indirect transitions, and this has limited similar in-depth studies of biexcitons. Here, we study biexciton emission in bilayer WS2 grown by chemical vapor deposition as a function of temperature. A biexciton binding energy of 36 4 meV is measured in the as-grown bilayer WS2 containing 0.4% biaxial strain as determined by Raman spectroscopy. The biexciton emission was difficult to detect when the WS2 was transferred to another substrate to release the stain. Density functional theory calculations show that 0.4% of tensile strain lowers the direct band gap by about 55 meV without significant change to the indirect band gap, which can cause an increase in the quantum yield of direct exciton transitions and the emission from biexcitons formed by two direct gap excitons. We find that the biexciton emission decreases dramatically with increased temperature due to the thermal dissociation, with an activation energy of 26 5 meV. These results show how strain can be used to tune the many-body effects in bilayered TMD materials and extend the photonic applications beyond pure monolayer systems.